“Not for the Weak or Fainthearted”: Lived Experiences of Nurses On-Call to Active Duty in the Armed Forces of the Philippines during the COVID-19 Pandemic (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
The outbreak of Coronavirus Disease 2019 (COVID-19) has underscored the crucial role of healthcare workers in the global fight against infectious diseases. Nurses, in particular, have been at the forefront of managing and preventing the spread of the virus. This responsibility became even more pronounced for nurses in the Armed Forces of the Philippines (AFP), who were exposed to severe risks during the pandemic. This study delves into the lived experiences of AFP nurses on active duty during the COVID-19 pandemic, using Husserlian phenomenology as the research approach.The research employed a qualitative approach, specifically Husserlian phenomenology, to explore nurses' experiences on active duty in the AFP during the COVID-19 pandemic. A purposive sampling method was utilized to select nine participants who could provide valuable insights into their experiences. Thematic analysis was applied to analyze the collected data.Six essential themes emerged from the thematic analysis:• Patrolling: This theme encapsulated the nurses' initial fear, anxiety, and shock when faced with the virus. It also highlighted the importance of training in preparing them for the challenges ahead.• Battleground: Nurses on active duty faced unsecured safety and a lack of resources, yet they felt a deep obligation and responsibility to go to work and care for COVID-19 patients.• Danger Areas: This theme encompassed the challenges of Enhanced Community Quarantine, isolation, and encounters with family members, underscoring the emotional toll of the pandemic.• Patrol Base: The nurses' faith in God, ability to overcome difficulties, and sense of being survivors were central to this theme.• Pride and Pleasure: Despite the hardships, the nurses always maintained a sense of thankfulness and happiness, exemplifying optimism, self-fulfillment, and contentment.• Victory: This theme celebrated strong leadership, passion, dedication, responsibility, patience, self-confidence, camaraderie, and teamwork as vital components of achieving success in adversity.The themes that emerged from the study underscore the remarkable dedication and resilience of nurses serving in the AFP during the COVID-19 pandemic. These nurses faced unprecedented challenges akin to those encountered by rangers in specialized military operations. The comparison to rangers, who engage in anti-guerrilla operations, counterterrorism, hostage rescue, unconventional warfare, and various combat scenarios, highlights the nurses' commitment to battling an invisible enemy in unpredictable conditions.The motto, “Not for the weak or fainthearted,” aptly characterizes rangers and AFP nurses. It encapsulates the extraordinary commitment and courage required to confront the unknown, whether on a battlefield or in a healthcare setting during a pandemic.Nurses in the AFP have played a pivotal role in the fight against COVID-19, facing a unique set of challenges. The study’s phenomenological approach illuminated the lived experiences of these healthcare professionals, providing valuable insights into their dedication and resilience. By likening them to rangers who thrive in unpredictable and often dangerous conditions, we gain a deeper appreciation of the courage and commitment of AFP nurses in their battle against an unseen enemy. This research contributes to our understanding of the experiences of healthcare workers during the pandemic, emphasizing the importance of their role in safeguarding public health.
Keywords: COVID-19 Pandemic; Nurses'Lived Experiences; Armed Forces of the Philippines (AFP); Husserlian Phenomenology; Rangers'Dedication and Resilience